Potential of field crickets meal (Gryllus bimaculatus) in the diet of African catfish (Clarias gariepinus) - Taufek, Norhidayah Mohd; Muin, Hasniyati; Raji, Ameenat Abiodun; Md Yusof, Hanan; Alias, Zazali; Razak, Shaharudin Ab (Taylor & Francis, 2018)
This study was conducted to evaluate the effect of dietary replacement of fishmeal (FM) by using field crickets (CM) and on growth performance and feed utilization of African catfish fingerlings. Five isonitrogenous diets (28% crude protein) were used containing 0% (control), 25%, 50%, 75% or 100% of FM substituted by CM. Triplicate group of fish (n = 15) were fed with their respective diets with initial mean body weight (BW) of 4.00 ± 0.8 g (mean ± SE) for 56 days. Fish fed with 100% CM exhibited significantly lower food conversion ratio than the lower inclusion level. Values of specific growth rate and protein efficiency ratio increased gradually with increasing amount of CM inclusion level from 50% to 100%. All compounds of essential amino acids were present in experimental diets although methionine, lysine and tryptophan were comparatively less than the required amount of amino acid for African catfish. Whole-body crude protein composition was significantly higher in fish fed with diet 50% to 100% CM compared to initial fish. These results indicated that CM is capable of serving as an alternative protein replacement for FM in the diet of farmed African catfish up to 100% without affecting body composition and feed utilization.